HOLOCAUST HISTORY, HOLOCAUST MEMORY ([S.l.])
1 online resource
Keywords: This volume is both a study of the history of Polish Jews and Jewish Poland before, during, and immediately after the Holocaust and a collection of personal explorations focusing on the historians who write about these subjects. While the first three parts of the book focus on "text," the broad nature of Polish Jewish history surrounding the Holocaust, the last section focuses on subtext, the personal and professional experiences of scholars who have devoted years to researching and writing about Polish Jewry. The beginning sections present a variety of case studies on wartime and postwar Polish Jews, drawing on new research and local history. The final part is a reflection on family memory, where scholars discuss their connections to Holocaust history and its impact on their current lives and research. Viewed together, the combination sheds light on both history and historians: the challenges of dealing with the history of an unparalleled cataclysm, and the personal questions and dilemmas that its study raises for many of the historians engaged in it. Holocaust History, Holocaust Memory is a unique resource that will appeal to students and scholars studying the Second World War, Jewish and Polish history, and family history.